New perspectives on HTML, XHTML, and XML comprehensive - Carey, Patrick (Course Technology/Cengage Learning, 2010)
NEW PERSPECTIVES ON CREATING WEB PAGES WITH HTML, XHTML, AND XML teaches students how to create simple to complex Web sites from scratch using HTML, XHTML, and XML.